THE REASON OF INDIA’S GOVERNMENT WHICH DECIDED TO APPLY BOLLYWOOD MOVIES AS ELEMENT OF SOFT DIPLOMACY IN INDONESIA - Ana Rizkia Umami (HI 16 UMY, 2016)
India is the state that have so many culture, one of the culture is Bollywood. Bollywood movie contain of the culture of India. India’s government apply Bollywood movie as the soft diplomacy to Indonesia. The Bollywood Fever in Indonesia is so booming. There are some fact stated that India and Indonesia has good relation since first India’s seller come to Indonesioa. They bring india’s culture to Indonesia. This paper will analyze the reasons behind India’s government which aplly the Bollywood mobie as soft diplomacy to Indonesia. It involves cultural diplomcy, national interest, and decision making process concepts to find the reasons. First, the paper will prove that the reason of India’s government apply the Bollywood movies as soft diplomacy to Indonesia is because it has values of culture, art, religion, morals, knowledge and other customs of India. Seconde is Bollywood got positive responses from the International public. The third is Bollywood movies increased gradually and India’s government saw this as the opportunity to get its economy and spread the culture. Keywords: Bollywood Movie, Bollywood Fever, India, Indonesia, Soft Diplomacy, National Interest, Foreign Policy, Culture, Economy. Introduction